Next generation strategy for tuning the thermoresponsive properties of micellar and hydrogel drug delivery vehicles using ionic liquids. Issue 16 (4th April 2022) - Shmool, Talia A.; Constantinou, Anna P.; Jirkas, Andreas; Zhao, Chen; Georgiou, Theoni K.; Hallett, Jason P.
Abstract : Thermoresponsive ionic liquid hydrogel delivery vehicles of reduced gelation temperature for injectable and controlled drug delivery applications. Abstract : Amongst the greatest challenges in developing injectable controlled thermoresponsive micellar and hydrogel drug delivery vehicles include tuning the cloud point (CP) and reducing the gelation temperature ( T gel ), below 37 °C, without compromising stability and solubility. Here, a unique strategy is employed using ionic liquid (IL) matrices to produce stable micellar and hydrogel delivery vehicles of distinct thermoresponsive properties. Each formulation includes the in-house synthesised polymer OEGMA30020 - b -BuMA22 - b -DEGMA11 with FITC-IgG. Both micellar-IL and hydrogel-IL formulations exhibit enhanced stability following 120 days of storage under 4 °C compared to in phosphate buffered saline (PBS). Visual tests demonstrate that the CP of the micellar-IL carriers can be finely tuned (31–46 °C). Rheology measurements show that hydrogel strength is significantly increased and T gel is reduced from 40 °C in PBS to 30 °C with IL. Finally, a unique stabilisation mechanism is proposed, triggered by the synergetic action of the excipients and IL in each system.